PENGARUH PENAMBAHAN ABU SISA PEMBAKARAN BATU BATA DAN SILIKA FUME TERHADAP KUAT TEKAN BETON PADA MUTU FC 33,2 MPA - A Rivai, Masri; Jonizar, Jonizar; Diastara, Rajib (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
This research is a concrete research that uses a mixture of Ash Combustion Remaining Bricks and Silica Fume in a cement mixture. This study was aimed to determine the effect of the addition of brick combustion ash and silica fume as cement additives on the compressive strength of concrete. This study used an experimental method with a total of 20 test specimen is the specimen. The test object consisted of normal concrete without additives as a comparison with a mixture of 4% Bricks Burning Ash and 1%, 2%, and 3% Silica Fume as cement additives. Each of the variations of the concrete mixture consists of 5 test objects. The test object is in the form of a cube with a size of 15 cm x 15 cm x 15 cm. Planned concrete quality is the K-400 or Fc’ 33.2 Mpa and compressive strength test performed at 28 days. From the results of the research conducted, the compressive strength test value of concrete obtained from a mixture of 4% Bricks Burning Ash + 3% Silica Fume is 391.2 Kg/Cm2. It can be concluded that from the addition of Silica Fume to 4% Ash of the Burning Bricks, it decreased from normal concrete.